The National Direct-Drive Program: OMEGA to the National Ignition Facility. (17th February 2018) - Regan, S. P.; Goncharov, V. N.; Sangster, T. C.; Campbell, E. M.; Betti, R.; Anderson, K. S.; Bernat, T.; Bose, A.; Boehly, T. R.; Bonino, M. J.; Cao, D.; Chapman, R.; et al.
Abstract: The goal of the National Direct-Drive Program is to demonstrate and understand the physics of laser direct drive (LDD). Efforts are underway on OMEGA for the 100-Gbar Campaign to demonstrate and understand the physics for hot-spot conditions and formation relevant for ignition at the 1-MJ scale, and on the National Ignition Facility to develop an understanding of the direct-drive physics at long scale lengths for the MJ Direct-Drive Campaign. The strategy of the National Direct-Drive Program is described; the requirements for the deuterium-tritium cryogenic fill-tube target being developed for OMEGA are presented; and preliminary LDD implosion measurements of hydrodynamic mixing seeded by laser imprint, the target-mounting stalk, and microscopic surface debris are reported.